Mulheres marceneiras e autogestão na economia solidária : aspectos transformadores e obstáculos a serem transpostos na incubação em assentamento rural - Cherfem, Carolina Orquiza (2009)
The Present research aimed to investigate the developing process of a self sustained community carpenter s workshop called Madeirarte, from Pirituba II settlement, located in Itapeva / SP. Madeirarte began from a community housing project done in the settlement, where the carpenter s workshop was built in order to make the housing parts and materials. This workshop was led by a group of four agriculturist women aged over forty-five years-old. These women began the community venture assuming that it could provide jobs and profits. In this context, the general concepts in this paper correlated to gender relations on the perspective of a dialogic feminism and the mutual economy in the self sustainable perspective. The first is due to the specificity of the job of women who work in carpentry, which is historically related to a concept of men s job, in the midst of a society where we observe the uneven relation between men and women and also among women themselves. The second is attributed to the context of a undertaking based on the mutual economy. Such economy corresponds to a quest of alternative ways to develop a productive processes that embraces solidariety, being able to connect the business activity to the real possibility of improving their quality of life, hence opposing the predominant capitalist ideology. Thus, this investigation aimed to reflect and dialog about the settlement process of Madeirarte by focusing on the gender relations and identifying the components of transformation and the components that come as obstacles, in order to find ways to improve the everyday life in their carpenter s workshop routine. For that, this paper established the concept of Dialogical Learning as a theoretical-ethodological basis, according to the guidelines of Habermas (1987), about the communicative action and, in the concept of dialogicity, developed by Paulo Freire (1994, 2005), by conceiving persons as essential subjects of a dialog, besides that they are engaged in the social context hence they are able to change it. The methodology used was the critical communicative approach, based on changing perspectives evidenced by the intersubjectivity and reflection as well as the importance of dialog in the knowledge building, which implies explicitness in the interpretation of the research subjects themselves. Thus, from the spaces of dialog established during the research, followed by the data collection structured by the analysis of the field diaries, interviews, participatory observation and communicative groups, the achieved results allowed us to interpret the reality experienced by the women carpenters in their everyday activities, connecting the work possibilities to the personal changes achieved around the settlement as well. The results also let identify the changing elements present at Madeirarte, by disclosing many acquired abilities and educational process built by women on the self sustained job. The research also identified the elements that appears as obstacles in this activity and pointing the possibilities to overcome. Finally, we seek to contribute with other settlement process and contribute through the women s best practices involved in community undertakings, such women who became roler models in their own lives, showing that it is necessary to expose the exclusion process that we live in but also to make known the possibilities of historical changes.